Reproductive behavior and seasonal occurrence of Psecas viridipurpureus (Salticidae, Araneae) - ROSSA-FERES, D. de C. [UNESP]; ROMERO, G. Q. [UNESP]; GONÇALVES-DE- FREITAS, E. [UNESP]; FERES, R. J. F. [UNESP] (Instituto Internacional de Ecologia, 2000)
O comportamento reprodutivo e a ocorrência sazonal de Psecas viridipurpureus foram estudados na Estação Ecológica do Noroeste Paulista, uma pequena área de conservação na região noroeste do Estado de São Paulo, Brasil (49º22'50W e 20º48'36S). P. viridipurpureus ocorreu em gravatás, uma bromeliácea (Bromelia balansae, Bromeliaceae) que não acumula água de chuva. Durante a exibição de corte, o casal ocupou a região mediana das folhas de gravatás, com o macho sempre localizado em uma posição superior à da fêmea. Os machos de P. viridipurpureus apresentaram um comportamento de corte complexo, que incluiu cinco padrões motores. O comportamento de corte e a cópula ocorreram preponderantemente durante a estação chuvosa e o recrutamento de jovens entre dezembro e julho. O abrigo de P. viridipurpureus difere do padrão de Salticidae, pois as ootecas são recobertas por uma cobertura de seda plana e não são incluídas em casulos.

The reproductive behavior and the seasonal occurrence of Psecas viridipurpureus were studied at the Estação Ecológica do Noroeste Paulista, a small conservation area in the northwest region of São Paulo State, Brazil (49°22'50''W and 20°48'36''S). P. viridipurpureus occurred on gravatá, a bromeliaceous plant (Bromelia balansae, Bromeliaceae) which does not accumulate rain water. During the courtship display the couple occupied the median region of the gravatá leaves, with the male always located in a higher position than the female. The males of P. viridipurpureus showed a complex courtship behavior, which included five motor patterns. The courtship and mating behavior occurred preponderantly during the rainy season and the juvenile recruitment between December and July. The retreat of P. viridipurpureus differs from the Salticidae pattern, since the egg sacs are covered with a plain silk cover and are not wrapped in cocoons.
Comportamento reprodutivo e ocorrência sazonal de Psecas viridipurpureus (Salticidae, Araneae)
Keywords: ocorrência sazonal; comportamento de corte; biologia reprodutiva; Salticidae; Psecas viridipurpureus; seasonal occurrence; courtship behavior; reproductive biology; Salticidae; Psecas viridipurpureus